Ursodeoxycholyl lysophosphatidylethanolamide protects against CD95/FAS-induced fulminant hepatitis - Utaipan, Tanyarath; Gan-Schreier, Hongying; Pathil-Warth, Anita; Stremmel, Wolfgang; Chamulitrat, Walee (Shock, 2017)
ABSTRACT: Increased activation of CD95/Fas by Fas ligand in viral hepatitis and autoimmunity is involved in pathogenesis of fulminant hepatitis and liver failure. We designed a bile-acid phospholipid conjugate ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE with LPE containing oleate at the sn-1) as a hepatoprotectant that was shown to protect against fulminant hepatitis induced by endotoxin. We herein further assessed the ability of UDCA-LPE to prevent death receptor CD95/Fas-induced fulminant hepatitis. C57BL/6 mice were intravenously administered with CD95/Fas agonistic monoclonal antibody (Jo-2) with or without 1 h pretreatment with 50 mg/kg UDCA-LPE. Jo-2 administration caused massive hepatocyte damage as seen by histology, and this was associated with a significant decrease in hepatic phosphatidylcholine (PC), lysoPC, and lysophosphatidylethanolamine levels. By histology, UDCA-LPE pretreatment improved hepatocyte damage and restored the loss of these phospholipids in part by a mechanism involving an inhibition of cytosolic phospholipaseA2 expression. Accordingly, Jo-2 treatment increased hepatic expression of cleaved caspase 8, caspase 3, and poly (ADP-Ribose) polymerase-1, and on the other hand decreased that of anti-apoptotic cellular FLICE-inhibitory protein. UDCA-LPE pretreatment was able to reverse all these changes. Moreover, UDCA-LPE attenuated inflammatory response by lowering the levels of Jo-2-induced proinflammatory cytokines TNF-α, IL-6, and IL-1β in liver and serum. UDCA-LPE was also able to decrease the levels of stimulated Th1/Th17 cytokines in Jo-2-primed isolated splenocytes. Taken together, UDCA-LPE exhibited potent anti-inflammatory effects against CD95/Fas-induced fulminant hepatitis.